The importance of pharmaceutical care in patients on antiretroviral drugs: an integrative literature review (2017-2022) (Research, Society and Development, 2022)
Pharmaceutical assistance is defined by the Brazilian government as a set of actions intended to promote, protect and recover public, individual or collective health, with medicines as the main means for this purpose. This article makes an integrative review of the literature that deals specifically with the importance of pharmaceutical assistance in antiretroviral treatments, finding these articles by searching the PubMed and Scielo repositories for the keywords “antiretroviral pharmaceutical assistance”, “antiretroviral assistance”, “antiretroviral pharmacy”, “antiretroviral pharmacy assistance” and “antiretroviral pharmacy” published between 2017 and 2022. It is concluded that there is great importance in pharmaceutical care as a way to support treatments, raising awareness and supporting patients to follow up responsibly on their antiretroviral treatments, understanding how beneficial this is for quality of life.